(untitled) (Experimental biology, 2020)
Potatoes are in fourth place in global crop production, after wheat, rice and corn. In connection with the nutritional value of this crop it is necessary to apply modern methods of biotechnology, in particular, editing the genome of this crop. For this, an effective system of in vitro direct regeneration is an important step for further successful use of this technology. As a result of experiments, optimal culture media have been selected to obtain direct regeneration from local potato cultivars. The most effective medium containing 1.0 mg/l zeatin, 7 mg/l gibberellic acid and 0.1 mg/l IAA was identified from eight media variants with different combinations and concentrations of phytohormones. Regenerate plants were obtained from all varieties. Stem explants had the highest regenerative capacity as compared to leaf explants. The number of micro shoots from one explant varied from 1 to 25 depending on the variety and variant of culture medium for direct regeneration. Thus, the Kazakh potato cultivars possessed higher ability to direct organogenesis, forming many shoots on one explant. Key words: direct regeneration, potato, domestic cultivars, regenerant, in vitro.